2000
DOI: 10.1021/es9906498
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Formation of Chlorinated Dibenzo-p-dioxins, Dibenzofurans, Biphenyls, Benzenes, and Phenols during MSW Combustion

Abstract: The aim of this study was to investigate how the levels and homologue profiles of organic micropollutants (OMPs) were effected by the so-called secondary formation between 650 and 200 °C. The combustion experiments were performed in a laboratory scale reactor fed with an artificial municipal solid waste fuel. The predominance of higher chlorinated OMP homologues after the secondary reaction shows that further chlorination reactions of OMPs formed at higher temperature reactions (>650 °C) are more important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 24 publications
6
40
0
Order By: Relevance
“…The results from a test program on a mixed feed under controlled conditions undertaken by Marklund's group at Umeå university provide some of the most comprehensive data available [56][57][58][59][60][61][62][63][64][65][66][67][68]. The tests involved burning 5 kg h −1 of artificial MSW in a pilot-scale fluidised bed.…”
Section: Homogeneous (Gas-phase) Reactions (500-800 • C)mentioning
confidence: 99%
“…The results from a test program on a mixed feed under controlled conditions undertaken by Marklund's group at Umeå university provide some of the most comprehensive data available [56][57][58][59][60][61][62][63][64][65][66][67][68]. The tests involved burning 5 kg h −1 of artificial MSW in a pilot-scale fluidised bed.…”
Section: Homogeneous (Gas-phase) Reactions (500-800 • C)mentioning
confidence: 99%
“…Two nonsubstituted phenol moieties present in the ash/residue condense to dibenzofuran followed by chlorination/ dechlorination reactions during the formation of PCDFs (Cains et al 1997). Wikstrom and Marklund (2000) suggested that PCDFs are formed by non/low chlorinated precursor followed by further chlorination/dechlorination reactions. During the formation of PCDD/Fs from PAHs, the formation of PCDFs dominated every homologue with a PCDD/Fs ratio of approximately 10 (Iino et al 1999).…”
Section: Polychlorinated Dibenzo-p-dioxin and Dibenzofuran (Pcdd/fs)mentioning
confidence: 99%
“…Incineration is the most commonly used treatment method for HCB, which can be almost completely destroyed; however, the by-products such as polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzop-furans (PCDFs) pollutants may be generated and will increase the risk of cancer [6]. As an alternative method to combustion technologies, mechanochemistry destruction have received a lot of attention and has many advantages for the destruction of HCB, such as non-combustion and solvent-free, low energy consumption and its possible implementation process [7].…”
Section: Introductionmentioning
confidence: 99%